Deviant behavior variety scale: development and validation with a sample of Portuguese adolescents - Sanches,Cristina (2016)
Abstract This study presents the development and analysis of the psychometric properties of the Deviant Behavior Variety Scale (DBVS). Participants were 861 Portuguese adolescents (54 % female), aged between 12 and 19 years old. Two alternative models were tested using Confirmatory Factor Analysis. Although both models showed good fit indexes, the two-factor model didn’t presented discriminant validity. Further results provided evidence for the factorial and the convergent validity of the single-factor structure of the DVBS, which has also shown good internal consistency. Criterion validity was evaluated through the association with related variables, such as age and school failure, as well as the scale’s ability to capture group differences, namely between genders and school retentions, and finally by comparing a sub-group of convicted adolescents with a group of non-convicted ones regarding their engagement in delinquent activities. Overall, the scale presented good psychometric properties, with results supporting that the DBVS is a valid and reliable self-reported measure to evaluate adolescents’ involvement in deviance.